Pectus excavatum, not always as harmless as it seems - Winkens, Ron (BMJ Publishing Group, 2009)
Pectus excavatum is usually considered meaningless and without clinical significance. The following case may put a different complexion on the matter. A healthy 59-year-old male patient complained of progressive heart palpitations, fatigue and postural dyspnoea; bending over caused a clear increase of dyspnoea. At repeated examinations no overt abnormality or explanation was found, except a supraventricular arrhythmia and a nodal tachycardia. In the years to follow the symptoms led to considerable physical impairments. Finally, the patient himself, after searching the web, came up with a possible cause: his pectus excavatum. A lateral chest x-ray with the patient bending over and a lateral computed tomography of the thorax revealed an impression of the heart by the sternum. Ten years after the patient’s signs and symptoms first appeared, a modified Ravitch procedure was carried out, after which the physical condition of the patient improved rapidly.